COGNITIVE DEVELOPMENT IN THE DIGITAL AGE: IMPLICATIONS OF SCREEN TIME AND LEARNING APPS IN CHILDREN'S THINKING PROCESS - Mesra, Romi; Neviyarni, Neviyarni; Mudjiran, Mudjiran (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2022)
This study aims to explore the impact of screen time and digital learning applications on children's cognitive development in the Indonesian context, focusing on the interaction between technology use, learning patterns, and socio-cultural factors. The research methodology uses a systematic literature review approach with the PRISMA protocol, analyzing 120 articles from 1,250 initial search results in the Scopus, Web of Science, ERIC, PsycINFO, and Google Scholar databases for the period 2018-2024. The results show patterns of digital technology use that vary based on geographic location (urban: 6.5 hours/day; rural: 3.2 hours/day) and socio-economic status, with a non-linear impact on cognitive function where moderate use (2-4 hours/day) shows a positive effect on visual-spatial and problem-solving abilities. The role of parental mediation, integration of local cultural elements, and balance between digital and non-digital activities emerge as key factors in optimizing the positive impact of digital technology on children's cognitive development.